Konversi Buku Ajar Pendidikan Agama Islam ( PAI) SMP Menjadi Modul Berbasis Contextual Learning - Wajihan Nihaya; Nurzannah Nurzannah (Jurnal Manajemen Akuntansi (JUMSI), 2023)
One of the integral parts of the national curriculum is religious learning. In Indonesia itself, the subject of Islamic Religious Education is required to be studied by students from elementary, middle, high school, to tertiary level, both in formal and non-formal schools, especially in schools that In fact, this madrasah research uses a qualitative descriptive method, which is a research method that utilizes qualitative data and is described descriptively. Research related to the conversion of Islamic Religious Education textbooks has produced a product in the form of a learning module for class 7 at junior high school level which specifically focuses on odd semester material and consists of 5 chapters. The process of converting textbooks into modules requires several stages to reach the finishing process.